2019
DOI: 10.1101/826578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timeless couples G quadruplex detection with processing by DDX11 during DNA replication

Abstract: & equal contribution2 Regions of the genome with the potential to form secondary structure pose a frequent and significant impediment to DNA replication and must be actively managed in order to preserve genetic and epigenetic integrity. The fork protection complex (FPC), a conserved group of replisome-associated proteins including Timeless, Tipin, and Claspin, plays an important role in maintaining efficient replisome activation, ensuring optimum fork rates, sister chromatid cohesion and checkpoint function. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 79 publications
(116 reference statements)
1
22
0
Order By: Relevance
“…It would be interesting to extend the theory in Ref. [58] to the present case to study how the rheology of nonspherical particles differs from that of spherical ones.…”
Section: Summary and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It would be interesting to extend the theory in Ref. [58] to the present case to study how the rheology of nonspherical particles differs from that of spherical ones.…”
Section: Summary and Discussionmentioning
confidence: 94%
“…An interesting question is how this difference affects the steady-state rheology near the jamming transition point. For spherical particles, it has been shown that the minimal eigenfrequency of D(ω) controls the viscosity near the jamming transition point [58]. It would be interesting to extend the theory in Ref.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…G4 motifs are quite common in genomes, with over 700,000 sites in the human genome. A new study by the Sale and Pellegrini laboratories (Lerner et al , ) has provided a significant step forward in understanding how the replisome senses G4 DNA in order to facilitate G4 unwinding and replication.…”
Section: A Model For How Timeless Could Detect G4 Dna Motifsmentioning
confidence: 99%
“…Now, the new data from Lerner et al () shed light on how Timeless/Tof1 can facilitate replication through DNA structures. The authors identify a myb‐like DNA‐binding domain in the C‐terminus of Timeless that preferentially binds to G4 DNA with ten‐times higher affinity than to duplex DNA.…”
Section: A Model For How Timeless Could Detect G4 Dna Motifsmentioning
confidence: 99%
See 1 more Smart Citation